Kebun Pintar dalam Ruang Berbasis Internet of Things - Ardiansyah, Vicky; -, Thiang; Putro, Iwan Handoyo (Jurnal Teknik Elektro Indonesia, 2024)
The concept of smart farming emerged as a sign that technology developments in the agricultural sector are growing rapidly. Home gardening activities have become a trend during the pandemic and are often still done manually. This research aims to create a prototype of an indoor smart garden that is connected via the Blynk application to control and display sensor readings. The plant used as a test was a peppermint plant with a testing period of 4 weeks with 2 different treatments. Based on the results of the overall system testing that has been carried out, the monitoring and control system can work well. The soil moisture sensor is prone to corrosion, so it needs to be replaced every 6-7 days. Peppermint plants, in the second test which were given a set point of soil moisture of 60% and provided light for 23 hours, experienced an increase in plant height, the color of the leaves is green and number of leaves increases when compared to the first test which was given a set point of soil moisture of 50% and provided light for 9 hours.